The Utilization of Mg-Al/Cu as Selective Adsorbent for Cationic Synthetic Dyes - Arini Fousty Badri; Neza Rahayu Palapa; Risfidian Mohadi; Mardiyanto Mardiyanto; Fitri Suryani Arsyad; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Mg-Al-LDH is a chemical compound produced through co-precipitation technique and modified with Cu(NO3)2.6H2O to form Mg-Al/Cu. However, the research on the capability of these compounds for adsorbing mixtures of cationic dyes as well as malachite green (MG), methylene blue (MB), and Rodhamine-B (Rh-B) has not been carried out. Therefore, this research aims to determine the performance of Mg-Al-LDH and Mg-Al/Cu for removing cationic dyes. The materials used were characterized by using XRD powder, FT-IR, and N2 adsorption desorption. The Adsorption process was conducted by batch system and several effects were investigated, such as kinetic parameter, isotherm, and the temperature condition. The stability feature of Mg-Al-LDH and Mg-Al/Cu was obtained from the regeneration process in the five cycles. The results presented that Mg-Al/Cu was effectively produced, which was indicated by the formation of layer at 10.792° (003), 22.94° (006), 35.53° (112), 55.78° (110), and 56.59° (116). Mg-Al-LDH and Mg-Al/Cu were found to adsorbed MG than the other cationic dyes with adsorption capacity of 68.996 mg/g and 104.167 mg/g, respectively. The unique properties of Mg-Al/Cu includes, structural stability towards the reuse of adsorbent subsequently for five times, without significant decrease of adsorption capacity. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).